Teachers' perceptions of how attention-deficit/hyperactivity disorder may influence learners' career choices - Maree, J. G.; Warnock, K. (South African Journal of Higher Education, 2023)
This article reports on teachers’ perceptions of how ADHD may influence learners’ career choices. Purposive selection was used to identify six high school teachers who cater specifically for learners with Attention-Deficit/Hyperactivity Disorder (ADHD). An exploratory case study design and a qualitative approach were adopted. Data was gathered using an audio-recorded semi-structured focus group interview, and analysed and interpreted using inductive thematic analysis. Findings suggest teachers believe that ADHD affects parents, schooling, and the school environment from an early age, that taking medication for ADHD from an early age may positively and negatively influence affect learners’ career choices, and that intervention to address the longer-term impact of ADHD on learners’ career choices is essential. Moreover, teachers believe that parents play a powerful role in the career choice of learners with ADHD. Future research should include early childhood carers, teachers and other health professionals, and include larger and more diverse groups of participants.